A Model For Achieving Urban Resiliency Imaginary And Explaining Its Relation With Poverty - Sharifzadegan, M. H.; Ramezani, R. (University of Eloued جامعة الوادي, 2016)
In order to reduce the risks of disasters, we need to establish theories to make seemingly disordered events, as logical phenomena. In fact, theory is like a map for reducing, answering and recovering from disasters. This subject is by the way, an exception because theory needs to be verified based on its immediate usage. This is a kind of necessity based on which problems of disasters, immediate response and reduction of risks must be answered so we cannot just make the theory and wish for it to become practical some day in future. Resilience in Urban and Regional Studies discussions is in search of special local properties that decrease vulnerability of urban areas. This is rooted in disaster confrontation studies so notion of resilience has more main limitation in answering the social-economic challenges. One of the most important challenges is confronting with poverty notion. Poverty, on one hand, reduces resilience because of increasing vulnerability, and on the other hand, poor locals regenerate vulnerable environments due to their high social correlations. The present study aims at investigating and analysis of theoretical and practical features in addition to recognized the dimensions of these two notions and their relation, plus extracting the main common concepts and indices of the relationship. Findings of the study show that governance concepts, social capital, social learning, social participation, institutionalism and vulnerability are among the intermediate rings in defining the relationship between poverty and resilience.
Article in Journal of Fundamental and Applied Sciences Vol 08, N 03
Keywords: notion, resilience, poverty, vulnerability, disasters